Relationship between Fifth Grade Students’ Reading Interest and Reading Ability - Aisyah, Siti; Purnamasari, Ratih (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
The purpose of this study was to determine the relationship between reading interest and students' reading comprehension ability. Research approach using quantitative with correlational study method. The subjects of this study were students of class VA and VB at SD Negeri Karya Bhakti totaling 90 students. The sample was taken by 47 students, then this study was obtained using a five-scale questionnaire for the Reading Interest and Reading Comprehension Ability variables using tests. Therefore, from the data obtained, it was found that a moderate relationship between reading interest and reading comprehension ability was seen from the accumulated calculation results, which was 30% such as using the time to read books in the library, while 70% is influenced by other factors such as students who are motivated by the teacher to increase reading interest so that students can to read a comprehension and other factors are also influenced from outside of students, namely when doing tasks, students are guided and assisted by parents. . Based on the results of the research above, it can be concluded that there is a positive relationship between Reading Interest and Reading Comprehension Ability in class VA and VB students of SD Negeri Karya Bhakti Odd semester of the 2019/2020 academic year.